Proceedings of the 2017 International Conference on Manufacturing Engineering and Intelligent Materials (ICMEIM 2017) 2017
DOI: 10.2991/icmeim-17.2017.41
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Diesel Cetane Number Using Near Infrared Spectra and Multivariate Calibration

Abstract: Abstract.Near infrared spectroscopy (NIRS) was investigated for measurement of diesel cetane. Three types of pretreatments including standard normal variate (SNV), multiplicative scattering correction (MSC) and Savitzky-Golay smoothing combining first derivative were adopted to eliminate the system noises and external disturbances. Then, partial least squares (PLS) and least squares-support vector machine (LS-SVM) methods were implemented for calibration models. Simultaneously, the performance of least squares… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
1
1
0
Order By: Relevance
“…The developed model uses 9 LVs to explain by about 99% the variance of the studied property. Considering the most recent studies regarding the estimation of diesel cetane number from NIR spectroscopy, the model developed in this study presents an RMSEP (2.0) comparable to the one obtained by Zhan et al [20] (2.0) but presenting a better r²P (0.96 vs. 0.55). Additionally, compared to the regression method employed by them (LS-SVM), by using the PLS method in this study, the obtained model was interpretable, helping to understand the chemical information of the total effluent having an impact on the diesel cetane number.…”
Section: Model Performance Analysissupporting
confidence: 70%
See 1 more Smart Citation
“…The developed model uses 9 LVs to explain by about 99% the variance of the studied property. Considering the most recent studies regarding the estimation of diesel cetane number from NIR spectroscopy, the model developed in this study presents an RMSEP (2.0) comparable to the one obtained by Zhan et al [20] (2.0) but presenting a better r²P (0.96 vs. 0.55). Additionally, compared to the regression method employed by them (LS-SVM), by using the PLS method in this study, the obtained model was interpretable, helping to understand the chemical information of the total effluent having an impact on the diesel cetane number.…”
Section: Model Performance Analysissupporting
confidence: 70%
“…Regarding the diesel cetane number estimation using NIR spectroscopy, the most recent studies are reported by Zhan et al [20] and Barra et al [21]. In the first study, a least squares-support vector machine (LS-SVM) regression model was developed with errors of calibration (1.8) and prediction (2.0) lower than the reproducibility of the ASTM D613-01 standard method (~3.3).…”
Section: Figure 1 Workflow Scheme For the Characterization Of Fuels O...mentioning
confidence: 99%